2019
DOI: 10.1029/2019gl085072
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Video Observations of Natural Lightning Attachment Process With Framing Rates up to Half a Million Frames per Second

Abstract: Using high‐speed video cameras operating with framing rates of 20 and 525 kfps, we imaged the attachment process of a natural negative cloud‐to‐ground flash, occurring at a distance of 490 m. Nine upward leaders were observed. A total of 12 space stems/leaders in 47 steps of the downward negative stepped leader were captured. The two‐dimensional length of them was between 2.0 and 5.9 m, with an average of 3.0 m. The average interstep interval, step length, and two‐dimensional speed of the downward negative lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…Qi et al (2016) recorded 23 space leaders in a natural lightning stepped-leader occurring 1-8 m ahead of the downward leader tip with lengths of 1-13 m. Jiang et al (2017) observed 31 space leaders occurring, on average, 3.6 m ahead of the leader tip. Srivastava et al (2019) and Qi et al (2019) reported average space-leader lengths of 2.1 and 3 m, respectively. Note that all lengths and distances in the studies discussed above are two-dimensional (2-D).…”
Section: Insights On Space-leader Characteristics and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al (2016) recorded 23 space leaders in a natural lightning stepped-leader occurring 1-8 m ahead of the downward leader tip with lengths of 1-13 m. Jiang et al (2017) observed 31 space leaders occurring, on average, 3.6 m ahead of the leader tip. Srivastava et al (2019) and Qi et al (2019) reported average space-leader lengths of 2.1 and 3 m, respectively. Note that all lengths and distances in the studies discussed above are two-dimensional (2-D).…”
Section: Insights On Space-leader Characteristics and Evolutionmentioning
confidence: 99%
“…(2019) and Qi et al. (2019) reported average space‐leader lengths of 2.1 and 3 m, respectively. Note that all lengths and distances in the studies discussed above are two‐dimensional (2‐D).…”
Section: Introductionmentioning
confidence: 97%
“…Qi et al. (2019) estimated the SDs of four lightning flashes terminated on a building with 100 m height. Note that, the above studies on the SD were obtained from the optical observations of lightning flashes striking a particular object with a certain height.…”
Section: Introductionmentioning
confidence: 99%
“…Visacro et al (2017) discussed different approaches to estimate the SD and reported SDs of 17 cloud-to-ground lightning flashes striking a 60 m high grounded structure. Qi et al (2019) estimated the SDs of four lightning flashes terminated on a building with 100 m height. Note that, the above studies on the SD were obtained from the optical observations of lightning flashes striking a particular object with a certain height.…”
mentioning
confidence: 99%
“…However, most of the studies on the characterization of CG flashes are performed using electric and magnetic field measurement systems, perhaps because of the high cost of high‐speed cameras. Another reason could be the smaller coverage area of high‐speed cameras (from 350 m to about 17 km, e.g., (Qi et al., 2018, 2019; Tran & Rakov, 2015, 2017; Wang et al., 2020)) in comparison with field measurements (from few meters to hundreds of kilometers, e.g., (Haddad et al., 2012; Leal & Rakov, 2021a, 2021b; Y. Zhu, Rakov et al., 2015)).…”
Section: Introductionmentioning
confidence: 99%